Toward an adaptive learning assessment pathway - Machkour, Mounia; El Jihaoui, Mohamed; Lamalif, Latifa; Faris, Sophia; Mansouri, Khalifa (Frontiers in Education, 2025)
The purpose of this study is to investigate how an adaptive assessment pathway can contribute to promoting personalized learning and improving access to education for all learners, regardless of their individual learning styles, paces, or needs. The study suggests a personalized learning assessment plan incorporating differentiated pedagogy and Universal Design for Learning (UDL). We conduct the experiment using the Moodle platform, taking advantage of Information and Communication Technologies (ICT) to reach a larger number of learners. The research used a mixed methodology to qualitatively analyze traditional learning assessment pathways’ limitations and quantitatively examine the proposed adaptive pathway’s impact on learning outcomes. While the results show a significant improvement in learning outcomes (88.9% improvement in Text study, 50% in Language activity, 55.6% in Writing, 80.6% in Total Control, and 77.8% in Oral production), the study also highlights the need for further research into the mechanisms, strategies, tools, approaches, issues, and future prospects associated with learning assessment.